1990
DOI: 10.1063/1.458647
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic friction on rigid and flexible bonds

Abstract: A wide variety of problems involving molecular motion in liquids can be formulated in terms of the generalized Langevin equation (GLE). The friction coefficient on a molecular bond or on some more complicated reaction coordinate is then required. An often used approximation is to set the dynamic friction constant equal to the autocorrelation function of the fluctuating force exerted on the frozen bond by the remaining unfrozen coordinates. The true friction involves projection operators and should differ from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 24 publications
3
129
0
Order By: Relevance
“…The potential of mean force, W͑r͒, of the ion pair in the presence of the solvent can then be calculated as 39 W͑r ͒ϭϪ ͵ F͑r ͒drϭW͑ r 0 ͒Ϫ ͵ r 0 r F͑r ͒dr. ͑7͒…”
Section: That Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of mean force, W͑r͒, of the ion pair in the presence of the solvent can then be calculated as 39 W͑r ͒ϭϪ ͵ F͑r ͒drϭW͑ r 0 ͒Ϫ ͵ r 0 r F͑r ͒dr. ͑7͒…”
Section: That Ismentioning
confidence: 99%
“…35 The equations of motion were solved numerically using the Verlet algorithm 38 using a time step of 0.5 fs. For the system consisting of two ions ͑A,B͒ and N solvent molecules, the force due to the solute-solvent interactions, acting along the interionic axis is evaluated as 39 ⌬F͑r,t ͒ϭ ͫ where F AS (r,t) and F BS (r,t) are the total forces on the solute particles A and B due to the solvent molecules; m A and m B are the individual masses of the ions; is the reduced mass of the ion pair and r is the unit vector along the AB direction. The ⌬F(r,t) values are calculated at each time step and then averaged over the whole simulation.…”
Section: Details Of the Simulationsmentioning
confidence: 99%
“…The simplest (and least chemically important) process of this type is self-diffusion. Other, more complicated (and, chemically, more important) examples include vibrational relaxation, [1][2][3][4] solvation dynamics, 5,6 and quadrupolar relaxation. 7,8 A starting point for many theories of self-diffusion is kinetic theory.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic mass and size of the diatomic solute are the same as those of an argon atom. In this table, the theoretical prediction is compared both with the simulation results of Berne et al 5 and the INM predictions. 6 In Ref.…”
Section: ͑15͒mentioning
confidence: 99%
“…2 Equation ͑4͒ gives a simple way to relate the solvent dynamic response to the VER rate. The validity of the freedraining approximation is systematically examined by Berne et al using molecular dynamics simulations 5 and the Zwanzig-Bixon model based on the continuous hydrodynamic equation, 8 and it is found that the approximation is not verified for a short bond length. However, this approximation is still semiquantitatively reliable, and so is the LandauTeller expression, at least for the low-frequency mode.…”
Section: Introductionmentioning
confidence: 99%